Board of directors and firm performance in mining companies: Mediating analysis of intellectual capital and sustainability reporting - Tutik Arniati; Muslichah Muslichah (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2023)
Purpose — This study aims to analyze the direct and indirect effects of board of directors on firm performance.Method — This study focuses on a population of mining sector companies that went public on the Indonesia Stock Exchange between 2019 and 2021. We analyzed a sample of 30 such companies. Our independent variable is the role of the board of directors, while the dependent variable is the performance of the company. We further examined intellectual capital and sustainability reporting as mediating variables. For our analysis, we employed the Partial Least Squares method using the SmartPLS version 3 software.Result — This study elucidates that while independent board directors do not directly influence a firm's performance, they significantly impact its intellectual capital, comprising knowledge, experience, intellectual property, and employee capabilities. This intellectual capital directly influences the firm's performance, suggesting an indirect route by which independent directors contribute to the firm's success. Moreover, independent directors also directly affect the firm's sustainability reporting, encompassing the disclosure of its economic, environmental, and social impacts. Like intellectual capital, sustainability reporting also impacts the firm's performance, providing another indirect pathway for independent directors to affect performance. Thus, intellectual capital and sustainability reporting serve as mediators between independent directors and firm performance, underscoring the crucial, albeit indirect, role these directors play in propelling a firm's success.Contribution — This research provides a valuable contribution to the academic community. First, this study integrates previous research into one research model. Second, this study examines sustainability reports as a mediating variable that is rarely studied.